Organizational Culture at PT Kereta Api Indonesia (Persero) Based on the Level of Basic Assumptions, Values, and Artifacts - Destyananda, Nanditya Putri; Suaedi, Falih (Jurnal Manajemen Publik dan Kebijakan Publik (JMPKP), 2022)
This study aims to determine the organizational culture applied at PT Kereta Api Indonesia (Persero) based on the level of organizational culture, namely: basic assumptions, values, and artifacts. Organizational culture plays a major function in modeling the behavior and performance of the company through the collective efforts of each member. The research method used is qualitative with emphasis on documentation as a data collection technique in this study. Meanwhile, data analysis was carried out in a narrative manner. The empirical findings in this study focus on organizational culture at PT Kereta Api Indonesia (Persero) which as a whole shows the company's success in improving management and employee performance. In addition, it has a significant impact on customer satisfaction and the good image of the company. PT Kereta Api Indonesia (Persero) provides excellent service to customers, where they are a top priority for the company. The change in orientation to excellent service to customers makes PT Kereta Api Indonesia (Persero) able to compete in the global market era.Keywords: organizational culture; PT Kereta Api Indonesia (Persero); organizational culture level